Cooperative MIMO Communication in Constrained Wireless Ad Hoc Networks - Bani, Hemanti; J.D, Bhosale (International Journal of Emerging Trends in Science and Technology, 2014)
In this paper, we investigate the issue of cooperative node selection in MIMO communications for wireless ad hoc networks, where a source node is surrounded by multiple neighbors and all of them are equipped with a single antenna. Given constraints such as energy, delay and data rate, a source node dynamically chooses its cooperating nodes from its neighbors to form a virtual MIMO system with the destination node (which is assumed to have multiple antennas), as well as adaptively allocates the power level and adjusts the constellation size for each of the selected cooperative nodes. In order to optimize system performance, we jointly consider the optimization of all these parameters with given system constraints. We assume that the source node either has CSI, or has no CSI. Heuristic algorithms, such as maximal channel gain (MCG) and least channel correlation (LCC) algorithms are proposed in order to exploit available system information and to solve the constrained optimization problem.Â Â Keywords: Cooperative/virtual MIMO, ad hoc, correlation, QR decomposition, channel state information (CSI).